Describing Nonfatal Intimate Partner Strangulation Presentation and Evaluation in a Community-Based Hospital: Partnerships Between the Emergency Department and In-House Advocates. Issue 1 (January 2022) - Bergin, Audrey; Blumenfeld, Elizabeth; Anderson, Jocelyn C.; Campbell, Jacquelyn C.; Patch, Michelle
Abstract : Objective: To describe characteristics of strangulation, and associated medical care, documentation, and injuries of women after nonfatal intimate partner strangulation (NF-IPS) who present for care to a community-based emergency department (ED) with an associated intimate partner violence (IPV) advocacy program between 2008 and 2016. Setting, Design, and Participants: A retrospective review of 345 female ED patients' medical records who sought care at a community hospital ED following a physical assault including strangulation by an intimate partner was conducted. Demographics, characteristics related to reported signs and symptoms, injuries, and subsequent imaging, diagnoses, and discharge information were abstracted. Results: Commonly reported symptoms were neck pain (67.2%) and headache (45.8%), with fewer patients reporting more severe symptoms such as loss of consciousness (22.6%), dysphagia (25.0%), or dysphonia (26.7%). Rates of patients disclosing strangulation to the entire multidisciplinary team and dedicated neck imaging appeared to improve between 2008 and 2014. Among the 45 patients with noted head and neck findings, 2 patients were found to have an internal carotid artery dissection, 2 patients were found to have strokes, and 1 patient was found to have an intracranial hemorrhage. Conclusions: Survivors of NF-IPS may present to community-based hospitals, and existing imaging guidelines can support clinicians in identifying serious internal injury such as carotid artery dissection and stroke. Further research is needed to better discern symptoms previously attributed to psychological trauma from poststrangulation brain injury. This study contributes to the growing literature on NF-IPS with data specific to community-based ED visits.